Predictive modeling of graves’ orbitopathy activity based on meibomian glands analysis using in vivo confocal microscopy - Zixuan Su; Yayan You; Shengnan Cheng; Jiahui Huang; Xueqing Liang; Xinghua Wang; Fagang Jiang (BMC Endocrine Disorders)
Abstract Objectives This study aims to identify indicators of disease activity in patients with graves’ orbitopathy (GO) by examining the microstructural characteristics of meibomian glands (MGs) and developed a diagnostic model. Methods We employed in vivo confocal microscopy (IVCM) to examine MGs in GO patients. Patients classified in the active phase were determined based on the clinical activity score (CAS). The research employed the least absolute shrinkage and selection operator (LASSO) method to select key indicators. Subsequently, a logistic regression model was constructed to predict GO disease activity. Results A total of 45 GO patients, corresponding to 90 eyes, were included in this study. A Lasso regression algorithm was utilized to select the predictor variables. Five predictor variables were included in our diagnostic model ultimately. The area under the curve (AUC) for the training set model reached 0.959, and for the validation set was 0.969. The training set and validation set models both demonstrated high accuracy in calibration. Finally, a Nomogram chart was constructed to visualize the diagnostic model. Conclusion We constructed a diagnostic model based on microstructural indicators of MGs obtained through IVCM and offered a clinical utility for assessing GO disease activity, aiding in the diagnosis and selection of treatment strategies for GO.